Klimatförändringar och dess effekter på ogräsfloran i Sverige - Henriksson, Jenny (SLU/Dept. of Crop Production Ecology, 2009)
Land management for food production is a fundamental human activity and one of the greatest challenges of the 21st century will be to increase the global food to accommodate a world growing to 10 billion or more people, while undergoing climate change. The increasing temperature and the current and projected increase in concentrations of CO2 lead to concern over possible impacts on agricultural pests. This assay is summarizing the knowledge of weeds in a changing climate in Sweden. Global warming and other climatic changes will affect the growth, phenology, and geographical distribution of weeds. The climate change will also affect the weed composition indirect by causing changes in the agriculture. Different types of crops may be possible to grow, there may be other cultivation measures and autumn sowing will be more common. Weeds that may be favored by the changing climate are for example those which are C3-plants, species with invasive characters, grass weeds and perennial weeds. As a result of a warmer climate the climate zones will be moving up north and there is a risk that troublesome weeds immigrate to Sweden. This movement up north will also appear among the already established weed flora of Sweden. There are still many questions unanswered and to be able to adapt the agriculture without troublesome weeds more locale research have to be done.